Braincase anatomy of the Paleocene crocodyliform Rhabdognathus revealed through high resolution computed tomography - Arthur Erb; Alan H. Turner (PeerJ, 2021)
Dyrosaurids were highly specialized, largely marine, relatives of living crocodylians, and one of the few archosaur lineages to survive the K-Pg extinction. Dyrosaurids lived during the Cretaceous to the Eocene and represent a unique combination of morphology and ecology not seen in living crocodylians. Little is known about their endocranial anatomy, leaving many questions about their neurosensory adaptations unaddressed. Recently, µCT (micro-computed tomography) scans were made of a well-preserved skull of Rhabdognathus, a Paleocene dyrosaurid from Mali. This marks the first time the braincase and neurosensory features of a dyrosaurid have been examined using CT. We focus our attention to three specific internal structures: the cranial endocast; the inner ear; and the paratympanic sinuses. The cranial endocast of Rhabdognathus revealed novel features including a unique conformation of its paratympanic system, a prominent dorsal venous system that communicates with the external skull table, extremely enlarged tympanic vestibules that meet at the midline of the endocranium, a prominent spherical cerebrum, and elongate olfactory tracts accounting for half the total endocast length. The bizarre laterally facing lateral Eustachian foramen of dyrosaurids is now understood to be a complex fossa including both a ventrally directed lateral Eustachian foramen and a laterally directed foramen for the basioccipital diverticulum. A novel median pterygopharyngeal canal was discovered connecting the pharynx to the adductor chamber. These revelations require a reinterpretation of the associated external foramina visible on the posterior of the skull in dyrosaurids and potentially their close relatives the pholidosaurids. The olfactory tract terminates in an enlarged olfactory region possessing complex bony projections—a unique morphology perhaps serving to increase surface area for olfaction. The inner ear of Rhabdognathus exhibits characteristics seen in both Pelagosaurus and Gavialis. The vestibule is spherical, as in Gavialis, but is significantly expanded. The semicircular canals are enlarged but pyramidal in shape as in the thalattosuchian Pelagosaurus. The proportion of the cochlear length to total endosseous labyrinth height is roughly 0.5 in Rhabdognathus implying that the hearing capabilities resemble that of thalattosuchians. A suite of expanded sense organs (e.g., bony olfactory lamina; hypertrophied vestibule of the inner ear), and the clear expansion of the cerebrum to a more symmetrical and spherical shape suggest that dyrosaurids possess neuroanatomical modifications facilitating an agile predatory near-shore ecology.